(untitled) (Fiep Bulletin - online, 2017)
The Project NATESC/UNIVILLE occurs to the school since 2005, with regular classes in swimming and twoevaluations anthropometric annually. During the practice period, the percentage of fat tends to decrease, but in the recess atschool these values increase. This factor suggests to establish a partnership with parents to encourage healthy habits. The goalwas to develop a swim program that prioritize work in a team - teachers, students, and parents – for the reduction and/or control ofbody weight of the adolescents and encourage healthy habits. The research was conducted with schoolchildren 10 to 13 years, ofthe schools public of Joinville-SC. The sample was composed of 19 boys and 20 girls. The data collected were weight, height,folds tricipital and subscapular skinfold. The protocols used were the Slaughter (1988) and the classification according toLohman (1987). As the instrument was considered to be the swim program and seminar awareness were conducted with theparents of the school. The Shapiro-Wilk test showed normality in all data, therefore, we adopted the Student t test for pairedsamples/independent and the test F. Contrary to what had been going on, this group of the sample showed decrease in thepercentage of fat during the school break. The female has decreased to 7.98% and the male 6,93% on the average. This resultmay be related with the lecture: "The Effect of Obesity in Pre-adolescents and Adolescents, and the importance of acquiringhealthy habits". It’s considered that there was the awareness of parents, encouraging the school positively in the regulation offeeding and in the practice of physical activities, helping to control the trend of increase in rates of obesity. In this study, the schoolof both sexes showed a decrease in the percentage of fat, according to the classification proposed by Lohman (1987).